Ronald Harms letter to James J. Dinsmore regarding bird sightings, June 26, 1986 - Harms, Ronaldet al (1986)
Field notes contributed by Ronald Harms in a letter to James J. Dinsmore. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of summer 1986. Epson - sheet feed/flatbed